2015
DOI: 10.1002/ejic.201500470
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Diiron Enzymes with a De Novo Designed Four‐Helix Bundle Structure

Abstract: A single polypeptide chain may provide an astronomical number of conformers. Nature selected only a trivial number of them through evolution, composing an alphabet of scaffolds, that can afford the complete set of chemical reactions needed to support life. These structural templates are so stable that they allow several mutations without disruption of the global folding, even having the ability to bind several exogenous cofactors. With this perspective, metal cofactors play a crucial role in the regulation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
95
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 177 publications
(294 reference statements)
2
95
0
6
Order By: Relevance
“…120-122 The overall results obtained on DF family demonstrated that the DF structure represents an excellent scaffold for hosting different activities. The earliest developed models have contributed to our understanding of the principles governing protein folding, stabilization, as well as metal coordination and substrate binding.…”
Section: Artificial Oxygen-activating Metalloenzymes By De Novo Dementioning
confidence: 99%
“…120-122 The overall results obtained on DF family demonstrated that the DF structure represents an excellent scaffold for hosting different activities. The earliest developed models have contributed to our understanding of the principles governing protein folding, stabilization, as well as metal coordination and substrate binding.…”
Section: Artificial Oxygen-activating Metalloenzymes By De Novo Dementioning
confidence: 99%
“…A possible way to construct artificial evolution pathways with such characteristics is the inverse protein folding, better known as protein design . Protein design consists in identifying sequences specific for a given backbone structure that at equilibrium would spontaneously adopt the target conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Our groups have designed the DF ( Due Ferri ) series of di-metal carboxylate bridged clusters stabilized helical bundles, 55,56 originally designed as mimics of diiron proteins. A number of versions of these proteins were prepared in which the four-helix bundle was assembled from four helical peptides, two helix-loop-helix peptides or a recombinantly expressed single-chain protein.…”
Section: Introductionmentioning
confidence: 99%